BROAD CONTEXT OF GENERAL EDUCATIONAL TRAINING OF CHOREOGRAPHY TEACHERS IN THE USA - Salo, Lesia (Studies in Comparative Education, 2018)
The article deals with the peculiarities of general educational training of choreography teachers in the US universities. The aim of the article is to analyze the content of choreography teachers' training in the USA, in particular general education program as its component. The content of choreography teachers' training in the USA on bachelor's level is examined. The detailed characteristics of education courses of foundation area of general education background, in particular: analytical reading and writing, intellectual heritage, quantitative literacy, is given. The results of education foreseen as consequences of mastering of these courses, are analyzed. The educational courses offered to students by the general education breadth background are considered in detail: arts, human behavior, race and diversity, science and technology, U.S. society, world society. The mechanism of creation of student's own educational trajectory, which is individual to every student, is found out. The brief description of the foundation courses of general educational training, that are practically-oriented and prepare students for the real-life and professional situations by mastering a series of competences has been made. The matrix of the correspondence of study results according to the foundation courses of general educational training to general competences of future choreography teachers in the USA has been presented.